Power storage: An important option for the German energy transition - Wolf-Peter Schill; Jochen Diekmann; Alexander Zerrahn (DIW Economic Bulletin, 2015)
The German energy transition makes it necessary to increase flexibility in the electricity system. Different forms of power storage may play a part in this, yet there is competition with other options on the production or demand side. In the short term, the further expansion of electricity generation from fluctuating renewables will be possible in Germany without additional power storage facilities. In the longer term, however, storage requirements will depend strongly on specific circumstances and are therefore difficult to predict. A model-based analysis shows that requirements for power storage rise sharply when the share of renewable energies is very high, particularly if other potential sources of flexibility are less developed. If options such as flexible generation of electricity from biomass, the enhancement of demand-side flexibility, or crossborder contributions to integrating renewable energies develop less favorably than is frequently assumed today, then additional electricity storage facilities will be required and economically beneficial in the long term. For this reason, supporting the development of power storage will be a useful component of a policy designed to safeguard the energy transition for the future. Policy-makers should aim for technological progress and cost reduction in power storage, primarily by means of continued and broad-based support for research and development. At the same time, policy should enable a level playing field for competition among the flexibility options in the various areas of application, for example on the control reserve market.
Keywords: Q42; Q47; Q48; 330; power storage; renewable energy; Germany